Plasma Medicine: A Field of Applied Redox Biology - VON Woedtke, Thomas; Schmidt, Anke; Bekeschus, Sander; Wende, Kristian; Weltmann, Klaus-Dieter (In vivo (Athens), 2019)
Plasma medicine comprises the application of physical plasma directly on or in the human body for therapeutic purposes. Three most important basic plasma effects are relevant for medical applications: i) inactivation of a broad spectrum of microorganisms, including multidrug-resistant pathogens, ii) stimulation of cell proliferation and angiogenesis with lower plasma treatment intensity, and iii) inactivation of cells by initialization of cell death with higher plasma treatment intensity, above all in cancer cells. Based on own published results as well as on monitoring of relevant literature the aim of this topical review is to summarize the state of the art in plasma medicine and connect it to redox biology. One of the most important results of basic research in plasma medicine is the insight that biological plasma effects are mainly mediated via reactive oxygen and nitrogen species influencing cellular redox-regulated processes. Plasma medicine can be considered a field of applied redox biology.